1923 Conn. Acts 3732 - (:unkn) unknown (My University, 1923)
Unnaturalized Persons, ch. 259, § 17: Prohibited noncitizens from owning or possessing any shotgun or rifle; violators subject to confiscation and resale of gun by state upon conviction.
Keywords: POSSESSION - DANGEROUS PERSONS